Recent advances in the Zymoseptoria tritici–wheat interaction: insights from pathogenomics - McDonald, Megan C.; McDonald, Bruce A.; Solomon, Peter S. (Frontiers in Plant Science, 2015)
We examine the contribution of next generation sequencing (NGS) to our understanding of the interaction between the fungal pathogen Zymoseptoria tritici and its wheat host. Recent interspecific whole genome comparisons between Z. tritici and its close relatives provide evidence that Z. tritici has undergone strong adaptive evolution, which is attributed to specialization by Z. tritici on wheat. We also assess the contribution of recent RNA sequencing datasets towards identifying pathogen genes and mechanisms critical for disease. While these studies have yet to report a major effector gene, they illustrate that assembling reads to the reference genome is a robust method to identify fungal transcripts from in planta infections. They also highlight the strong influence that the wheat cultivar has on effector gene expression. Lastly, we suggest future directions for NGS-guided approaches to address largely unanswered questions related to cultivar and lifecycle dependent gene expression and propose that future experiments with Z. tritici be conducted on a single wheat cultivar to enable comparisons across experiments.